Evaluation of OCL for Large-Scale Modelling: A Different View of the Mondex Purse - Aydal, Emine; Paige, Richard; Woodcock, Jim (Electronic Communications of the EASST, 2007)
OCL is used to add rigour to UML/MOF models, and inparticular can be used to express behavioural details (e.g.,operation pre- and postconditions, class invariants) of such models.The applicability and utility of OCL can be assessed by applying itto realistic applications and by investigating its capabilities bothin terms of language characteristics and tool support. With this inmind, in this paper we model functional requirements for the Mondex Smart Card Application using UML Diagrams, demonstrate how system invariants as well as operation pre- and post-conditions are specified in OCL, and explore the degree to which OCL tool support can be used to create and validate these models. Moreover, we discuss how these pre- and post-conditions can be validated, in part by discussing how test cases can be selected from the OCL specifications created.